Free will – an approach from the perspective of neuroscience - Adrian Sorin Mihalache; Leon Zagrean (Romanian Journal of Medical Practice, 2021)
Free will designates the possibility of conscious and free choice of the subject, as well as his real possibility to act. The topic has a special medical and social relevance as it is directly connected to how the subject’s responsibility (moral, legal, medical) for his own actions are understood, but also the possibility (real or illusory) of intervention in his own life. Free will has received various philosophical, psychological, legal and interdisciplinary approaches in recent decades. In this article we shall inventory some results from the area of neuroscience that we consider relevant in the analysis of free will, research and clinical studies that highlight various effects caused by voluntary actions, consciously repeated by the subject. Some psychotherapeutic interventions, the process of awareness, learning, attention monitoring, visualization, some forms of meditation, and the changes that these practices produce in the processes of neurogenesis, neuroplasticity and epigenetics, in terms of health and quality of life are analyzed. Since these interventions involve the conscious participation of the subject and his voluntary action, we consider that the discussed results are relevant in the debate on free will. The study also highlights the importance of education and social knowledge, as well as the need to promote participatory prevention and therapy, involving the subject in increasing the quality of life and health, through public messages that emphasize the responsibility of each person for their own choices and actions and the impact they have on his life.